Resíduo do beneficiamento de feijão em dietas para ovinos confinados - Ferro, Mariane Moreno (2014)
Aimed to evaluate the effect of inclusion of the residue from the processing of beans to replace cottonseed meal in diets for feedlot sheep. The experiment was conducted at the Federal University of Mato Grosso -campus Rondonópolis-MT. 16 sheep mongrel males with a mean age of 12 years and a mean weight of 30 kg, distributed in a completely randomized design with four treatments and four replicates were used in the experimental test. The diets were formulated to contain 45% forage and 55% concentrate on dry matter. The treatments consisted of the replacement of cottonseed meal per bean residue at levels of 0, 33, 66 and 100% in the concentrate. Diets were formulated to be isonitrogenous crude protein content of 14%. The experiment lasted twenty days and fifteen days for adaptation to the diets and environment and remaining five days to monitor the consumption and collections. We evaluated the consumption and digestibility of DM, OM and dietary nutrients, the kinetics of in vitro ruminal fermentation of food (elephant grass silage, soybean, bean residue, cottonseed meal, corn), the grazing behavior receiving the experimental diets. We also evaluated the use of internal indicators (MSi, NDFi, ADFi) and external (Cr2O3). Data were subjected to regression analysis, the choice of parameters based on the significance of the regression models and coefficients of determination. Inclusion levels of common bean residue to replace cottonseed meal altered the intake of DM, OM, CP, NDF and TDN significant quadratic response (P<0.05) intakes of 1221.94; 1142.97; 178,35; 471.17 and 888.29 g / day, respectively. EE intake in g / day, showed a linear decrease (P<0.05) increased as the levels of residue substitution of beans, whi le the CNF intake in g / day, increased linearly (P<0.05). The apparent digestibility of DM, OM, CP and CNF increased linearly (P<0.05) the digestibility of EE had no significant effect (P>0.05), while the digestibility of NDF showed quadratic effect (P<0.05) increased as the inclusion levels of common bean residue replacing the cotton cake, with 65.03% digestibility. The cumulative gas production ranged from 47.47 to 150.61 mL for cottonseed meal and corn meal. For the fraction of rapidly digested carbohydrates (CNF) were estimated ruminal volumes of gases ranging from 20.79 to 77.69 mL, respectively for cotton cake and bean residue. Digestion rates for the fraction of fast-digesting (CNF) ranging from 0.0307 to 0.1879 h-1 for napier grass silage and ground corn, respectively were estimated. For the fraction of slow digestion (B2), gas productions ranging from 26.25 to 81.10 mL, for cottonseed meal and ground corn, respectively were estimated. For the fraction of slow digestion (B2) digestion rates varying from 0.0182 to 0.0321 h-1 for the residue of crushed beans and corn were estimated. As the variables of ingestive behavior, the total time of supply (hours / day), leisure time (hours / day), efficiency of DM and NDF intake and rumination efficiency of MS showed a quadratic response (P<0.05), with 5.71 hours; 9.21 hours; MS 237.98 g / hour; 85.04 g NDF / hour and 145.54 g DM / hour. The total rumination time (hours / day) had no significant effect (P>0.05) as increased levels of substitution of cottonseed meal per residue beans with an average of 8.43 hours. The number of ruminated daily chewing time and number merícica diary ruminating chewing showed a quadratic effect (P<0.05) with 793.71 cakes / day; 14.73 hours; 50796.44 chews / day. Chewing time per bolus, the number of periods of eating, ruminating and idling showed no significant effect (P>0.05) with a mean of 41.12 second / cake; 33.56; 50.62 and 59.96 times / day. Regarding the use of indicators, there was no significant interaction (P>0.05) between diets and the use of indicators. The estimated fecal excretion (g / day) of the experimental diets used, regardless of the indicator showed no statistical difference (P>0.05) with an average of 371 g / day. The apparent digestibility quadractricaly signi ficant effect (P<0.05) between diets with maximum digestibility of 71.02%, regardless of the indicator used. To estimate fecal output (g / day) and apparent DM digestbilidade no statistical difference (P>0.05) when using internal indicators (MSi, NDFi, ADFi) and external (Cr2O3) averaging 371 g / day and 67.20%, respectively, regardless of the diet. The residue of beans can replace cottonseed meal by up to 60% in the concentrate. Indicators, internal and external, are efficient in estimating the faecal excretion and apparent digestibility.